Porto-spleno-mesenteric venous thrombosis after elective splenectomy: a retrospective cohort study - Baldari, Ludovica; Boni, Luigi; Giuliani, Beatrice; Cassinotti, Elisa (Frontiers in Immunology, 2023)
Background. Elective splenectomy is the main treatment for a wide range of haematological diseases. Porto-spleno-mesenteric venous thrombosis represents one of the most severe complications of this procedure. The aim of this study was to evaluate risk factors associated with development of portospleno-mesenteric venous thrombosis after elective splenectomy. Methods. All cases of elective splenectomy carried out from April 1 st 2017 to January 31 st 2023 were included in this single centre retrospective cohort study. Patients' demographics and perioperative data were analysed and correlated with the incidence of postoperative thrombosis. All patients underwent postoperative doppler ultrasound screening for thrombosis. Analysis was performed using SPSS 28, with p-value < 0.05 considered significant. Results. Twenty-two patients (10 women, 12 men) underwent splenectomy during the study period. Indications were: immune thrombocytopenia (n: 6), myeloproliferative disorder (n: 6), hereditary spherocytosis (n: 4), thalassemia (n: 1), lymphoma (n: 1), leukaemia (n: 1), other malignancies (n: 3). Six patients developed porto-spleno-mesenteric venous thrombosis and only 2 of them were symptomatic. Patients were treated with anticoagulation therapy with complete resolution. Analysis identified three main factors associated with thrombosis: spleen diameter (p = 0.03), myeloproliferative disorder (p = 0.02), intraoperative platelet transfusion (p = 0.002) and intraoperative red blood cells transfusion (p = 0.009).Standardized postoperative screening allows prompt diagnosis and treatment of portospleno-mesenteric venous thrombosis even in asymptomatic cases. Patient with splenomegaly and affected by myeloproliferative disorder have a greater risk to develop this complication.